السمات الشخصية لدى الأدباء المبدعين في الشعر اليمني المعاصر - Abdulnaser Hasan Dahnan
This research aims to identify the personality traits among contemporary Yemeni poets, evaluate the differences between these personality traits according to the following variables: age, gender, educational level, experience in poetry writing and geographical area, investigate the approach and circumstances experienced by the poets during the production process of the poetry as well as to discover some personality characteristics possessed by the poets during the poetry production. In order to achieve these goals, three tools were used: questionnaire, interview and content analysis. The questionnaire contained 73 items was to identify the personality traits among contemporary Yemeni poets and evaluate the differences between these personality traits according to the research variables. Purposive sampling was used and involved 39 poets who represent 30% of the population (N=130). The interview that consisted of 9 structured questions was to learn the approach and circumstances experienced by the poets during the production process of the poetry. Purposive sampling has involved 15 contemporary Yemeni poets who represent 38% of the main sample. Whereas Hie content analysis has evaluated descriptively 8 randomly chosen poems in order to identify the personality characteristics possessed by the poets during the poetry process. The results from questionnaire indicated that the personality traits among contemporary Yemeni poets were internal locus of control (=4hI.ll1 o~IjSy), more to neuroticism (<)l.ajj';ll U1y';ll) rath r than non-neuroticism (~L...:uJI), they are extraverion (~4';l1), less narcissism (~yJl) and with high level in achievement motivation (j4U)'1 ~b). This study also found that there are differences among contemporary Yemeni poets in term of two personality traits, emotional stability and achievement motivation according to the age. There is no significant difference in personality traits due to the gender and educational level among them. The exper1ence in poetry only influenced the emotional stability trait. The geograp ieal area has influenced locus of control and emotional stability traits. Whereby, the result from interview found that the contemporary Yemeni poets have experienced several intersecting stages until they complete the poetry production as every poem was produced gradually in stages. Concern and stress are two necessary feelings in the process of poem production beside affected by unconcious situation. There were many obstacles faced by the contemporary Yemeni poets that affected the process of poetry production. The content analysis found some personality characteristics possessed by the poets within the analyzed poems either through explicit or symbolic expression which include concern, stress, sentimental feelings, empathy, regression, projection, sublimation, regret, imagination and realism. This research suggests that attention should be given by relevant government agencies in Yemen especially for developing the contemporary Yemeni poets to enhance their abilities, skills, career and provide them with good opportunity to participate in programs and seminars that enable them to express their creativity beside conducting research and supporting them with material or moral efforts.